2021
DOI: 10.1007/s00405-021-07089-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidental uptake of fluorodeoxyglucose in the Waldeyer’s ring and risk of oropharyngeal malignancy

Abstract: Purpose Fluorodeoxyglucose (FDG) positron emission tomography (PET) is increasingly used to diagnose and stage malignancy. The aim of this article is to investigate the significance of incidental FDG uptake in the Waldeyer’s ring and to assess its value in predicting clinically occult oropharyngeal malignancy. Methods All FDG-PET/CT scans performed in Imperial College NHS Foundation Trust, UK between January 2012 and November 2018 were included. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Existing guidelines and reviews have examined the broader literature pertaining to incidental PETavid lesions. 2,11 Up to 11.7% of incidental lesions detected during the workup of an existing head and neck malignancy are located in the head and neck, and result in delays to treatment initiation and worsens overall survival outcomes. 18 In this comprehensive search of three major hospital databases, there were two unexpected malignancies identified in 31 patients undergoing surgery for PET-avidity in the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing guidelines and reviews have examined the broader literature pertaining to incidental PETavid lesions. 2,11 Up to 11.7% of incidental lesions detected during the workup of an existing head and neck malignancy are located in the head and neck, and result in delays to treatment initiation and worsens overall survival outcomes. 18 In this comprehensive search of three major hospital databases, there were two unexpected malignancies identified in 31 patients undergoing surgery for PET-avidity in the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…12 One study examining generalized uptake in Waldeyer's Ring in 102 patients undergoing surveillance PET for other malignancies noted only 1 event of metastatic oropharyngeal cancer. 11 Similarly, one retrospective study performed on surveillance PET for 592 patients with known lung cancer demonstrated only 10 patients with uptake in the oropharynx, of which there was one case of oropharyngeal osteosarcoma. 13 Furthermore, even in patients with pre-existing tonsillar malignancy, the significance of PET-avidity of the contralateral tonsil is uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Minor asymmetrical uptake is frequently seen in non-malignant tonsils. 32,33 There are no studies on the role of 18F FDG PET-CT specifically in the assessment of the contralateral neck in HNSCCUP. A meta-analysis of the role of 18F FDG PET-CT in detecting nodal metastasis in patients with HN SCC showed a sensitivity of 79% and specificity was 86%.…”
Section: -F Fdg Pet-ctmentioning
confidence: 99%
“…However, some malignant tonsils have normal FDG uptake; therefore, PET‐CT should not be used to exclude tonsillar cancer. 32 Minor asymmetrical uptake is frequently seen in non‐malignant tonsils 32,33 …”
Section: Accuracy Of Imaging Modalities In the Detection Of Hnsccupmentioning
confidence: 99%